2009
DOI: 10.1158/1078-0432.ccr-08-1719
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic Significance of p53 Codon 72 Polymorphism Differs with Race in Colorectal Adenocarcinoma

Abstract: Purpose Several studies have examined the prognostic value of the codon 72 polymorphism of the p53 gene in colorectal adenocarcinoma, but none have addressed patient race/ethnicity. Therefore, this study assessed the prognostic value of this polymorphism in African American and Caucasian colorectal adenocarcinoma patients separately. Experimental Design Colorectal adenocarcinomas from137 African Americans and 236 non-Hispanic Caucasians were assessed for p53 mutations and genotyped for the codon 72 polymorph… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
65
1
3

Year Published

2010
2010
2020
2020

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 79 publications
(74 citation statements)
references
References 54 publications
5
65
1
3
Order By: Relevance
“…Previous studies have implicated that both Arg and Pro alleles may be associated with the higher risk of malignancy. The risk of tumour progression in CRC patients considerably vary between racial and ethnic groups [6,13,17,18]. We found that frequency of genotype …”
Section: Discussionmentioning
confidence: 66%
See 2 more Smart Citations
“…Previous studies have implicated that both Arg and Pro alleles may be associated with the higher risk of malignancy. The risk of tumour progression in CRC patients considerably vary between racial and ethnic groups [6,13,17,18]. We found that frequency of genotype …”
Section: Discussionmentioning
confidence: 66%
“…A common SNP, referred to as Arg72Pro, is located in the proline-rich region in exon 4 in the segment of p53 [5] and encodes either an arginine amino acid (CGC, Arg72) or a proline residue (CCC, Pro72). This region is required for the growth suppression and apoptosis mediated by p53 but not for cell cycle arrest [6]. Arg72 form of p53 is a more efficient inducer of apoptosis than Pro72, and thus may increase the responsiveness to chemotherapy [7][8][9].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Of these, the codon 72 polymorphism (rs1042522) is by far the more common, which results in the substitution of arginine (Arg) by proline (Pro) in the transactivating domain.54Changes in its amino acid sequence can alter the ability of p53 to bind to receptors in target genes, alter DOI:http://dx.doi.org/10.7314/APJCP.2014.15.21.9171 Helicobacter pylori Infection and a P53 Codon 72 SNP: a Reason for an Unexplained Asian Enigma recognition motifs for post-translational modifications or alter p53 stability and interactions with other proteins (Walker and Levine, 1996;Thomas, 1999;Shepherd et al, 2002;Bergamaschi et al, 2003;Li and Prives, 2007). Such changes may contribute to tumor progression and a poor prognosis (Katkoori et al, 2009).…”
Section: Discussionmentioning
confidence: 99%
“…Racespecific differences in the frequency of TP53 alterations have been shown between colorectal patients of Afro-American and Caucasian origin, with the prevalence of mutations in the former, which were rs1042522 CC carriers. Surprisingly, the African American CC genotype was associated with a high risk of lymph node metastasis and increased mortality (Katkoori et al, 2009). Although the above evidence is small in number and needs further approval, calculation of the ethnic component is essential to perform accurate and qualitatively correct association studies.…”
Section: Tp53 Polymorphisms: the Cancer Predisposing Effect And Ethnimentioning
confidence: 99%